Tensor product model transformation based decoupled terminal sliding mode control. Issue 8 (10th June 2016) - Zhao, Guoliang; Li, Hongxing; Song, Zhankui
Abstract : The main objective of this paper is to propose a tensor product model transformation based decoupled terminal sliding mode controller design methodology. The methodology is divided into two steps. In the first step, tensor product model transformation is applied to the single-input-multi-output system and a parameter-varying weighted linear time-invariant system is obtained. Then, decoupled terminal sliding mode controller is designed based on the linear time-invariant systems. The main novelty of this paper is that the nonsingular terminal sliding mode control design is based on a numerical model rather than an analytical one. Finally, simulations are tested on cart-pole system and translational oscillations with a rotational actuator system.